The Effect of Camera and Display Technology on the Reliability of Digital Shade Evaluation - Aswini Kumar; Venkitachalam Ramanarayanan; D. Harikrishnan; Rahul Sajeev; Athira Rejithan; Vineetha Karuveettil; Reshma Suresh (Amrita Journal of Medicine)
Introduction: For a successful prosthodontic rehabilitation, accurate and economic shade selection methods are warranted. Shade selection with digital cameras and various commonly used digital displays can be suggested as an alternative to expensive colorimetric instruments and inaccurate visual shade selection. To digitalize prosthetic rehabilitation, standards need to be set on minimum digital specifications required to capture and communicate accurate shade selection. This study aimed to establish a minimum specification required for a digital image, to achieve the most accurate result in prosthodontic shade selection, using digital photography.